Cytomegalovirus sinusitis complicated by orbital apex syndrome in an immunocompromised host. Issue 6 (24th November 2016) - Nomura, Jim H.; Eichhorn, Knut; Cao, Thai M.; Sahebi, Firoozeh
Abstract: Sinusitis in immunocompromised patients can be caused by a wide variety of pathogens, primarily bacterial and fungal in nature. Tissue invasion can extend into the orbital apex and result in ophthalmoplegia and blindness. We report the first histologically proven case, to our knowledge, caused by cytomegalovirus infection.